TEKNOLOGI INFORMASI PERPUSTAKAAN - Yulinar Yulinar (UIN Imam Bonjol Padang, 2019)
Abstract : An important component of information technology besides hardware, software, human resources is the budget. The budget is needed to support the provision of information technology infrastructure and instruments as well as educate and train the readiness of human resources implementing information technology in libraries. The library is an information system that in the process there are activities of collecting, processing, preserving, preserving, and presenting. The application of information technology in the library is an integrated, mutually influencing part, and is related to the empowerment of libraries and librarians / library technical personnel. Libraries must continue to improve following the development of information technology and transform from the conventional way to an automated library and digital library.Keyword : Library Information TechnologyAbstrak : Komponen penting teknologi informasi selain perangkat kasar, perangkat lunak, sumber daya manusia adalah anggaran. Anggaran diperlukan untuk mendukung penyediaan infrastruktur dan instrument teknologi informasi serta mendidik dan melatih kesiapan sumber daya manusia yang mengimplementasikan teknologi informasi di perpustakaan. Perpustakaan merupakan sistem informasi yang dalam prosesnya terdapat aktivitas pengumpulan, pengolahan, pengawetan, pelestarian, dan penyajian. Penerapan teknologi informasi di perpustakaan merupakan bagian yang terintegrasi, saling mempengaruhi, dan berkaitan dengan pemberdayaan perpustakaan dan pustakawan/tenaga teknis perpustakaan. Perpustakaan harus terus berbenah mengikuti perkembangan teknologi informasi dan bertranformasi dari cara konvensional menuju perpustakaan berautomasi dan perpustakaan digital.Kata Kunci : Teknologi Informasi Perpustakaan